Examining cultural words translation in tourism texts: a systematic review - Chen, Shiyue; Mansor, Nor Shahila; Mooisan, Chin; Abdullah, Muhammad Alif Redzuan (Academy Publisher, 2023)
The steady growth of tourism is increasing the demand for tourism translation. Cultural words (CWs) translation is challenging since they are absent from target cultures. This systematic review examines studies on CWs translation in tourism texts to comprehend the literature and explore future research tendencies. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, researchers did a comprehensive literature review. Twenty-one articles met the inclusion criteria after the protocol-required data selection and screening. The findings reveal that scholars are increasingly concerned with CWs translation in tourism texts. Moreover, all the included articles used varied theories. Most of them focused on applying various taxonomies of translation strategies to compensate for the losses of cultural connotations in cultural words' rendition. Besides, other researchers focused on CWs translation from different perspectives, such as translation quality assessment, Eco-translatology, meaning equivalence, cultural manipulation, and relevance theory.